Field - grown transgenic wheat expressing the sunflower gene HaHB4 significantly outyields the wild type - González, Fernanda Gabriela (2019)
Fil: González, Fernanda Gabriela. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Pergamino (EEA Pergamino). Buenos Aires, Argentina.